2011
DOI: 10.1186/1753-6561-5-s4-s4
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal gene expression patterns correlate with severity of systemic infection in chicken

Abstract: BackgroundNot much is known about the effect of Salmonella enteritidis on changes in the developmental processes occurring in the intestine of young chicken. Therefore we investigated the correlation of intestinal gene expression patterns with the severity of systemic Salmonella infections.MethodsThe number of Salmonella colony forming units (CFUs) in the liver of infected chicken were plotted against the average intestinal expression profiles of previously identified gene expression clusters. The functional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…correlated the intestinal gene expression profiles with the severity of systemic S. Enteritidis infection in challenged chickens. Genes associated with metabolism, cell turnover, and tissue repair in the jejunum of challenged chickens were negatively correlated with the severity data, which was consistent with previous studies (Schokker et al , 2011 b , 2012). Further, the authors showed that the differences in the intestinal barrier functions and immunological responses were the underlying factors behind the varying susceptibility of different chicken breeds/lines to Salmonella infections.…”
Section: Transcriptomicssupporting
confidence: 91%
See 1 more Smart Citation
“…correlated the intestinal gene expression profiles with the severity of systemic S. Enteritidis infection in challenged chickens. Genes associated with metabolism, cell turnover, and tissue repair in the jejunum of challenged chickens were negatively correlated with the severity data, which was consistent with previous studies (Schokker et al , 2011 b , 2012). Further, the authors showed that the differences in the intestinal barrier functions and immunological responses were the underlying factors behind the varying susceptibility of different chicken breeds/lines to Salmonella infections.…”
Section: Transcriptomicssupporting
confidence: 91%
“…Transcriptomic techniques (microarrays and RNA-Seq) allow study of expression of organism's genes in different tissues, conditions, or time points (Lowe et al , 2017). Transcriptomics studies have led to better understanding of the pathophysiology and immunopathology of foodborne pathogens in poultry by analyzing the host cell's/tissue's responses, and local and systemic immune responses to the pathogen during infection (van Hemert et al ., 2006; Chiang et al ., 2008; Sandford et al ., 2011; Schokker et al ., 2011 a , 2011 b ; te Pas et al ., 2012; Huang et al ., 2016; Sun et al ., 2017 a ). Further, it allows elucidation of key features of the complex interactions between poultry and foodborne pathogens (Crépin et al , 2008; Palyada et al , 2009; Van Immerseel, 2010), and have led to the identification of host-resistance mechanisms (Hiett et al , 2008; Schokker et al , 2012; Xu et al , 2014) and the development of novel therapeutics such as microRNAs to control foodborne pathogens in poultry (Jia et al , 2016; Wu et al , 2017).…”
Section: Transcriptomicsmentioning
confidence: 99%
“…Even though nutrient absorption is a key physiological process, it happens quite rapidly—chyme passage time along jejunum is from 40 to 60 min.Due to availability of nutrients, jejunum is also target for both commensal bacteria and enteric pathogens. Shokker et al (2011) found correlation between Salmonella infection and jejunal gene expression [62]. Functions of jejunum in developing birds was characterized based on transcriptomic modulation; by day 21 post-hatching it was assigned to immune regulation [63].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid repetition with studies in which the transcriptional response to Salmonella in the intestine of rats [23,24], mouse [25], chicken [26,27], and pigs [9,28,29] was recorded after longer infection periods than 2 and 4 hours, the pathways/genes called significant after 8 hours were discussed briefly in the results section (section isogenic comparisons). In this discussion we focus on 2 and 4 hours genes/processes which may play a crucial role in the regulation of inflammation in the intestine in general.…”
Section: Discussionmentioning
confidence: 99%